Clinical presentations among adult patients with tuberculous meningitis - Ahmed, Kamal; Uddin Akhanji, Md Mubin; Islam, Md Shahidul; Ahasan Ahmed, K. M.; Islam , Md Zakirul (International Journal of Research in Medical Sciences, 2023)
Background: Bangladesh is a country with a high burden of pulmonary as well as extrapulmonary tuberculosis. TBM is a particularly important public health issue in our country. Identifying prognostic predictors would improve the quality of management and ultimately will prevent long-term mortality and morbidity. The aim of the study was to observe and identify the most common clinical presentations among patients with tuberculous meningitis. Methods: This hospital-based prospective cohort study was carried out at the in-patient Department of Clinical Neurology at the National Institute of Neurosciences and Hospital (NINS and H), Dhaka, Bangladesh from October 2016 to September 2017, 1 year. A total of 54 patients admitted to the hospital with features of tuberculous meningitis (TBM) were selected for the study following inclusion and exclusion criteria. Results: Over 70% of patients were adolescents or young adults with a mean age of 28.2±12.3 years. The majority (48.2%) of the participants were from TBM stage II, while 37% were from stage III of TBM. Fever, headache, and systematic symptoms were the most frequent clinical presentations. The median delay in treatment was 30 days. Interruption in anti-TB treatment was reported in 3 (9.3%) cases. Conclusions: The study found that among possible TBM cases, the most frequent clinical features were fever, headache, and systematic symptoms. Focal neurological deficit and cerebral nerve palsy also had a high prevalence among the participants. The majority of the participants were young adults and female prevalence was high in the present study. The majority were from stage II TB among the study participants.